CORRUPTION AS AN INSTITUTIONAL THREAT TO THE FORMATION AND DEVELOPMENT OF THE HUMAN RESOURCES OF PUBLIC ADMINISTRATION BODIES (Coordinates of Public Administration, 2026)
The article examines the phenomenon of corruption as an institutional threat to the formation and development of the personnel core of public administration bodies in Ukraine. It is emphasized that in the conditions of the modern stage of state-building, the issue of integrity, professionalism and openness of the civil service acquires special importance, because it is the personnel core that is the basis of the effectiveness of management processes and the stability of public power. It is noted that corruption deforms the system of selection, promotion and evaluation of civil servants, undermines the principles of meritocracy, reduces the effectiveness of personnel policy and contributes to the establishment of informal networks of influence.Based on the analysis of the regulatory framework of Ukraine and international acts, it is proven that, despite the presence of a sufficient legislative basis, the implementation of anti-corruption mechanisms in the personnel sector remains insufficiently effective. It is emphasized that corruption in the civil service leads to the formation of a closed, ineffective personnel environment that is devoid of innovative potential and the ability to reform.The article substantiates the need for a comprehensive approach to preventing corruption, which combines legal, organizational and ethical means of influence. The author proposes the main directions for improving personnel policy in the field of public administration: digitalization of personnel selection and evaluation procedures, increasing the role of public control, developing an ethical culture of civil servants, creating independent commissions on career advancement.The results of the study confirm that effective counteraction to corruption in the personnel sector is a key condition for the institutional stability of public authorities, restoring citizens' trust in the state and ensuring sustainable development. It is concluded that the formation of an honest, professional and responsible personnel core is a strategic task of the modern anti-corruption policy of Ukraine.